Construction demand and key technology development direction of underground gas storage in China - Xiaoping YANG (You-qi chuyun)
Low-carbon and clean energy is an urgent need for China to cope with the challenges at home and abroad in the process of energy development. Thus, natural gas as a low-carbon and clean energy is becoming more important in the national energy system. However, the problems of lagging gas storage infrastructure and insufficient reserve capacity have become the shortcomings that restrict the safe and stable supply of natural gas and the healthy development of the industry in China. The construction conditions of underground gas storage in China are poor, with many complex fault blocks, deep burial, poor reservoir physical properties and strong non-homogeneity. The complex geological conditions not only greatly improve the construction difficulty of underground gas storage in China, but also form a safety hazard for the gas storage, which poses a greater challenge to the theory, technology and engineering application of gas storage construction in China. Herein, the construction demand and the current technical status of underground gas storage in China were reviewed based on the current situation of gas storage demand and the geological conditions. Meanwhile, the gap between the domestic and foreign key technologies of underground gas storage was summarized from the following three aspects: the construction and operation technology of gas reservoir type gas storage, the stability evaluation technology of single well salt cavern construction and operation, and the construction technology of aquifer type gas storage. Finally, it was pointed out that it was necessary to focus on the scientific research on key technologies of gas storage construction, rapidly develop the underground gas storage construction, operation and safety early warning technology, so as to meet the long-term development needs of underground gas storage construction, and ensure the emergency peak regulation and gas supply safety of natural gas in China.